Petrology of Lava from The Maninjau Lake, West Sumatera - Bhakti H.Harahap; Hamdan Z.Abidin (Pusat Survei Geologi, 2006)
Andesitic lavas and rhyolitic tuffs are the main products of the Maninjau Lake during Pleistocene. The lava is distributed up to radius of 20 km, whiles the tuff 100 km that suggests a high explosive volcanic. The lava is exposed beautifully along the road from Bukit Tinggi to Lubuk Basung mapped as Qamj on the 1:250 000 geologic map of Padang Quadrangle. The lava is having sheeting joint in some parts, dark gray, highly porphyritic in texture with phenocrysts of plagioclase, clino- pyroxene, ortho-pyroxene and opaques. Quartz phenocryst occurs in rhyolite lavas that are rarely found in the area. Xenoliths of diorite are occurred in some andesite. The lavas have narrow range in silica composition ranging from 54-60 wt % and rarely up to 69 wt%. K2O versus SiO2 relationship shows that analyzed samples belong to calc-alkaline series which are mainly of high-K. While the trace element of the rocks is summarized on the spider diagram, here their patterns strongly resemble the typical of arc lavas with enrichment in large ion lithophile elements (LILE) and light rare earth elements (LREE) relative to high field strength elements (HFSE) and heavy REE (HREE). More over, these patterns show an Nb resembling the arc type magma commonly resulted from subduction, whether in island arc or active continental margin. The geochemical characteristic of the lava from Maninjau Lake is a lower concentration of Ba, Sr and La than other active continental margin like the Andes volcanic rocks. Like many other subducted related rocks, the andesite characterize a very evolved magma, where they have low MgO concentrations (3 wt%) with Mg# 30-53. According to the plate tectonic model, Sumatera is on the continental side to subduction process since Eocene until the present. The presence of subducted magma character in Maninjau Lake area was argued to have been accounted during the eastward subduction of the India-Australia Oceanic Crust. It seems also that Sumatra Fault Zone is a very important agent to conduit magma onto the surface in the Barisan Ranges including the lava resulted from Maninjau Lake.Â Keywords : Â petrology, andesitic lava, rhyolitic tuff, Maninjau, Pleistocene